Biocontrol of Fusarium oxysporum of banana using antagonistic bacteria - Nur Syahirah Abd Halim (2017)
Fusarium oxysporum is an omnipresent pathogen and is known as one of the soil-borne pathogens that causes serious disease to the plant. Fusarium oxysporum f. sp. cubense causes the fusarium wilt or know as panama disease in banana and it causes great loss in banana production. Usually, the farmer controls it through the application of chemical fungicide however it is not very effective and it also causes problems to environment, humans and animals. The uses of the chemical to overcome the problem are also not effective as the misused of the fungicide has created resistant population of the pathogen. Many researches have been conducted and reported in controlling fusarium wilt using biocontrol. In Malaysia, few researches has been documented on biological control of Fusarium wilt therefore, the application of biocontrol agent is very limited. The objective of the study is to evaluate the effect of the five antagonistic bacteria which are Bacillus subtilis strain and Bacillus licheniformis on mycelia growth of the Fusarium oxysporum f. sp. cubense. In vitro screening of the biological control activities of the Bacillus is conducted using the dual culture test, cultural filtrate test, double plate test and bi-layer test. The average of the percentage of inhibition of the pathogen for all the method is 60%. This shows that Bacillus spp. has the ability to control Fusarium oxysporum f. sp. cubense to control Fusarium wilt.